Distal Femur Locking Plates Fit Poorly Before and After Total Knee Arthroplasty. Issue 5 (May 2019) - Campbell, Sean T.; Bosch, Liam C.; Swinford, Steven; Amanatullah, Derek F.; Bishop, Julius A.; Gardner, Michael J.
Abstract : Objective: To evaluate the fit of distal femur locking plates. Secondarily, we sought to compare plate fit among patients with and without a total knee arthroplasty (TKA). Design: Retrospective. Setting: University hospital. Intervention: Standard length precontoured distal femur locking plates from 4 manufacturers were digitally templated onto each patient's pre-TKA and post-TKA radiographs. Main Outcome Measurements: The maximum distance from the plate to the lateral femoral cortex (plate-bone distance) was measured in the metaphyseal region. Mean plate-bone distances were compared between manufacturers and between pre-TKA and post-TKA radiographs. Results: All implants tested were undercontoured in all patients. Plate-bone distances ranged from 6.6 ± 0.4 mm to 8.0 ± 0.4 mm (mean ± SE) pre-TKA and 8.2 ± 0.3 mm to 8.6 ± 0.3 mm after TKA, indicating worse fit after arthroplasty ( P < 0.001). There were also intermanufacturer differences, with Synthes and Smith & Nephew implants demonstrating the lowest plate-bone distances in the pre-TKA and post-TKA groups, respectively. Proportionally, plate-bone increase was greater in the female cohort (16%) compared with the male cohort (8%). Conclusions: There was plate-bone mismatch for the distal femur locking plates tested in this study, due to undercontouring of the implants. After patients underwent TKA, poor implant fit was exacerbated. Surgeons must be aware of the potential for deformity if the proximal segment is brought into contact with the implant. These finding may help optimize implant design for the treatment of periprosthetic distal femur fractures.